Efficient broad-band emission from contorted purely corner-shared one dimensional (1D) organic lead halide perovskite - Biswas, Anupam; Bakthavatsalam, Rangarajan; Shaikh, Samir R.; Shinde, Aparna; Lohar, Amruta; Jena, Satyam; Gonnade, Rajesh G.; Kundu, Janardan (Chemistry of Materials, 2019)

Ligand structure directed dimensionality reduction (2D -> 1D) in lead bromide perovskite - Bakthavatsalam, Rangarajan; Haris, Muhammed P. U.; Shaikh, Samir R.; Lohar, Amruta; Mohanty, Ashutosh; Moghe, Dhanashree; Sharma, Shivani; Biswas, Chinmoy; Raavi, Sai Santhosh Kumar; Gonnade, Rajesh G.; Kundu, Janardan (Journal of Physical Chemistry C, 2020)
Low dimensional (2D, 1D) lead halide perovskites are currently attracting huge research interest due to their enabling properties. Demonstrating synthetic control on the dimensionality/ structure of these perovskites is highly challenging. Dimensionality in these perovskites is largely dictated by the nature/structure and composition of the incorporating ligands and the utilized synthetic conditions. Here, we demonstrate chemical composition based control on reduction of dimensionality (2D -> 1D) for lead bromide perovskite utilizing 2-(2-aminoethyl)isothiourea dihydrobromide as a common precursor ligand (Isothio Bromide). Controlling the hydrothermal reaction parameters (temperature, time) at a fixed precursor ratio affords corner-shared, contorted 2D sheet perovskite and corner-shared, contorted, chiral 1D chain perovskite. Such dimensionality reduction leads to contrasting photophysical properties: 1D chain perovskite shows long-lived and self-trapped broad band emission, whereas 2D perovskite shows short-lived, band edge emission with a long tail. Mechanistic studies and single crystal structure analysis reveal the incorporation of the utilized precursor ligand (Isothio Bromide) in 2D perovskite. Surprisingly, the 1D perovskite is found to be chiral (P2(1) space group) incorporating 2-(2-aminoethyldisulfanyl)ethanamine and ammonium ions as the achiral ligands generated in situ due to hydrothermal cleavage of the precursor (Isothio Bromide) ligand. Such structural and compositional change of the ligands, which manifests a different hydrogen bonding network in the resultant perovskite structure, plays a decisive role in dictating the final molecular formula and dimensionality/structure of the perovskite which largely controls their photophysical properties.